Column Adsorption and Desorption Studies of Fluoride on Perchloric Acid Cross-Linked Calcium Alginate Beads - Y. Vijaya; A. Krishnaiah (E-Journal of Chemistry)
Contamination of drinking water due to fluoride is a severe health hazard problem. Excess of fluoride (>1.5 mg/L) in drinking water is harmful to the human health. Various treatment technologies for removing fluoride from ground water have been investigated in the past. Present investigation aims to remove fluoride by perchloric acid cross-linked calcium alginate (PCA). Column flow adsorption data were utilized to obtain breakthrough curves and desorption experiment have been carried out with a view to recover the adsorbed fluoride and regenerate the PCA beads using 0.05 M EDTA. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) studies were used for the characterization of the adsorbent.